Structural Defense of Plants and Pathogenesis - Ekinci, Berkay; Ekinci, Berkay (01. Izmir Institute of Technology, 2023)
The major challenge in today s world is ensuring an adequate food supply for the growing global population. Achieving this goal requires the development of crops by using sustainable agricultural strategies in ecologically suitable areas (Jan et al. 2011; Doğanlar et al. 2023). However, plant diseases, which are caused by various pathogens such as bacteria, fungi, viruses, nematodes, and herbivores, pose a significant threat to crop quality and yield. Fortunately, plants have several preexisting and induced defense and immune mechanisms to protect themselves against biotic and abiotic stresses (Jones et al. 2006; Freeman et al. 2008). This review aims to provide information on phytopathogens, the steps of pathogenesis, plants’ pre-existing structural defense mechanisms against pathogenesis, and more. It is aimed at broadening the reader's knowledge and perspective by providing a wide range of examples, from simple to complex. I hope that this review will be a good start for enlightening and inspiring all curious scientists who, like me, are enthusiastic about this field.
A Review Written by 3rd Year Undergraduate Molecular Biology and Genetics Student at Izmir Institute of Technology
Keywords: Pathogens; Plant genetics; Plant pathogen